Cognitive problems among breast cancer survivors: loneliness enhances risk. Issue 12 (11th April 2014) - Jaremka, Lisa M.; Peng, Juan; Bornstein, Robert; Alfano, Catherine M.; Andridge, Rebecca R.; Povoski, Stephen P.; Lipari, Adele M.; Agnese, Doreen M.; Farrar, William B.; Yee, Lisa D.; Carson, William E.; Kiecolt‐Glaser, Janice K.
Abstract Background Cancer survivors often experience cognitive difficulties after treatment completion. Although chemotherapy enhances risk for cognitive problems, it is likely only one piece of a complex puzzle that explains survivors' cognitive functioning. Loneliness may be one psychosocial risk factor. The current studies included both subjective and objective cognitive measures and tested whether lonelier breast cancer survivors would have more concentration and memory complaints and experience more concentration difficulties than their less lonely counterparts. Methods The relationship between loneliness and cognitive function was tested among three samples of breast cancer survivors. Study 1 was a sample of breast cancer survivors (n = 200) who reported their concentration and memory problems. Study 2a was a sample of breast cancer survivors (n = 185) and noncancer controls (n = 93) who reported their concentration and memory problems. Study 2b was a subsample of Study 2a breast cancer survivors (n = 22) and noncancer controls (n = 21) who completed a standardized neuropsychological test assessing concentration. Results Studies 1 and 2a revealed that lonelier women reported more concentration and memory problems than less lonely women. Study 2b utilized a standardized neuropsychological continuous performance test and demonstrated that lonelier women experienced more concentration problems than their less lonely counterparts. Conclusions These studies demonstrated that loneliness is linked to concentration and memory complaints and the experience of concentration problems among breast cancer survivors. The results were also highly consistent across three samples of breast cancer survivors. These data suggest that loneliness may be a risk factor for cognitive difficulties among cancer survivors. Copyright © 2014 John Wiley & Sons, Ltd.